2015
DOI: 10.1038/cddis.2015.247
|View full text |Cite
|
Sign up to set email alerts
|

DEC1 regulates breast cancer cell proliferation by stabilizing cyclin E protein and delays the progression of cell cycle S phase

Abstract: Breast cancer that is accompanied by a high level of cyclin E expression usually exhibits poor prognosis and clinical outcome. Several factors are known to regulate the level of cyclin E during the cell cycle progression. The transcription factor DEC1 (also known as STRA13 and SHARP2) plays an important role in cell proliferation and apoptosis. Nevertheless, the mechanism of its role in cell proliferation is poorly understood. In this study, using the breast cancer cell lines MCF-7 and T47D, we showed that DEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 53 publications
(61 reference statements)
2
53
0
Order By: Relevance
“…Their expressions are positively related to histologic grade, invasion and resistance of tumors. The stable expression of cyclin E when only using α-bisabolol or radiotherapy may be due to the compensation effect of other molecular pathway [41][42][43] or the low dose we used, while it was significantly reduced when using α-bisabolol and radiotherapy together. Thus, the decrease we detected indicated that EC cells were suppressed, and the progression of EC was slowed by the combination of α-bisabolol and radiotherapy.…”
Section: Discussionmentioning
confidence: 92%
“…Their expressions are positively related to histologic grade, invasion and resistance of tumors. The stable expression of cyclin E when only using α-bisabolol or radiotherapy may be due to the compensation effect of other molecular pathway [41][42][43] or the low dose we used, while it was significantly reduced when using α-bisabolol and radiotherapy together. Thus, the decrease we detected indicated that EC cells were suppressed, and the progression of EC was slowed by the combination of α-bisabolol and radiotherapy.…”
Section: Discussionmentioning
confidence: 92%
“…The function of nuclear BHLHE40 was apparent from other studies, where nuclear BHLHE40 was up-regulated in MCF-7 estrogen receptor positive breast cancer cells www.Genes&Cancer.com upon paclitaxel treatment [103], suggesting that nuclear BHLHE40 prevent tumor progression. In contrast, cytoplasmic BHLHE40 bound to and stabilized cyclin E [104], thereby preventing its nuclear entry and inhibiting cell cycle progression, thus, an increase in cytoplasmic BHLHE40 is tumor suppressive. Therefore, in these cases, despite an upregulation, BHLHE40 may not play an oncogenic role.…”
Section: Differential Effect Of Bhlhe40 In the Nucleus And The Cytoplasmmentioning
confidence: 99%
“…BHLHE40 has primarily been reported to be involved in multiple biological functions, such as neurogenesis, apoptosis, cell proliferation and differentiation, and circadian rhythms . Recent studies have shown the diverse expression of BHLHE40 in different tumors and indicated the tissue specificity.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 BHLHE40 has primarily been reported to be involved in multiple biological functions, such as neurogenesis, apoptosis, cell proliferation and differentiation, and circadian rhythms. [8][9][10][11][12] Recent studies have shown the diverse expression of BHLHE40 in different tumors and indicated the tissue specificity. Compared with adjacent normal tissues, higher expression levels of BHLHE40 were found in most tumors (colon, oral, gastric, pancreatic, esophageal, liver cancer, and brain tumors) except for non-small-cell lung cancer.…”
mentioning
confidence: 99%